Goal Striving, Coping, and Well-Being: A Prospective Investigation of the Self-Concordance Model in Sport - Smith, A.; Ntoumanis, Nikos; Duda, J.; Vansteenkiste, M. (Human Kinetics, 2011)
Developing upon cross-sectional research (Smith, Ntoumanis, & Duda, 2007) supporting the self-concordance model (Sheldon & Elliot, 1999) as a framework for contextual goal striving, the current study investigated the assumptions of the model in relation to season-long goal striving in sport. The study additionally examined the role of coping strategies in the persistence of goal-directed effort. Structural equation modeling analysis with a sample of 97 British athletes indicated that start-of-season autonomous goal motives were linked to midseason effort, which subsequently predicted end-of-season goal attainment. Attainment was positively related to changes in psychological need satisfaction, which, in turn, predicted changes in emotional well-being. In a second model, autonomous and controlled motives positively predicted task- and disengagement-oriented coping strategies, respectively. In turn, these strategies were differentially associated with effort. The findings provide support for contextual adaptations of the self-concordance model and demonstrate the role of coping strategies in the goal striving process.